(untitled) (The Research of Medical Science Review, 2025)
Plants and plant-based substances are essential to microbial management programs, human health care, and animal health care. The development of innovative and potent antimicrobial drugs is currently crucial due to the increase in drug-resistant pathogens. Most people have thought about using medicinal herbs as a natural treatment for bacterial diseases. Medicinal plants can be used to make a variety of drugs. A substance with desired active characteristics that is extracted from plant tissue and usually treated with a solvent for a particular purpose is called a plant extract. In Khyber Pukhton Khuwa, there are numerous Dysphania ambrocoides (DA) and Berginia ciliate (BC) species. DA and BC are two traditional medicinal plants in Pakistan. This study aimed to ascertain the antibacterial activity of DA and BC extracts against four pathogenic bacteria: Salmonella typhi, Escherichia coli, Bacillus subtilus, and Staphylococcus aurous, using methanolic and distilled water extracts. The antibacterial activity of DA and BC was evaluated using the well diffusion and disc diffusion procedures. The synergistic effect of the combined extracts was evaluated using the same methods. Gram-negative bacteria were more effectively combated by them than gram-positive ones. The average zones of inhibition for Salmonella typhi 22, Escherichia coli 22, Staphylococcus aurous 16, and Bacillus subtilus 18.5 were calculated using the well diffusion method. In the disc diffusion method, the corresponding numbers for Salmonella typhi, Escherichia coli, Staphylococcus aurous, and Bacillus subtilis were 20–14, 19.3, and 17. Staphylococcus aurous, Salmonella typhi, Escherichia coli, and Bacillus subtilis were all effectively inhibited by the mixed extract. Extracts of Dysphania Ambrocoides leaves and Berginia ciliate roots were found to be potent antimicrobials. These findings suggest that DA and BC can be used as natural antimicrobials to treat bacterial infections either alone or in combination. Further research is needed to evaluate the extracts' mechanisms of action and safety and efficacy in vivo.